Resilience strategies in sustainable supply chain management: bibliometric analysis and future research directions / Shariffah Zatil Hidayah Syed Jamaludin ... [et al.] - Syed Jamaludin, Shariffah Zatil Hidayah; Mustapa, Muzani; Mohamad Ramly, Zuhaili; Muhammad, Norjuma'ah (UiTM Press, 2024)
The emergence of the volatile, uncertainty, complexity, and ambiguity (VUCA) has adversely affected the supply chain network's resilience. The risks and difficulties presented by the VUCA environment can harm an organisation's performance. The project stakeholders are highly encouraged to prioritise sustainability, adaptability, and resilience while considering the constantly changing, volatile, and uncertain climate. Thus, Sustainable Supply Chain Management (SSCM) is a strategic response to the challenges the VUCA environment poses. Contracting firms can expand their capacity to mitigate risks, negotiate volatility, and generate long-term value for all stakeholders by integrating sustainability concepts into supply chain operations. However, SSCM become problematic because of diverse global supply chain disruptions and sustainable demands. Understanding the trends in this topic is crucial to discovering the pattern of resilience strategies in sustainable supply chains. The current literature is reviewed in this study, focusing on studies conducted between 2006 and 2024. The Scopus database and the VOS viewer software were used to arrange a systematic literature review and provide an overview of this field. One hundred fifty-nine (159) publications on resilience, risk management and SSCM were identified and written by hundred and nine (109) authors from forty-four (44) countries. The top number of publications was from Iran, with thirty-eight (38), followed by the United States, with twenty-six (26). The most frequently used keywords are sustainability, supply chain management, supply chains, and sustainable development, reflecting the current significant research direction. Standard bibliometric indicators were utilised in this study, and data analysis was done using VOSviewer, Microsoft Excel, and Harzing's Publish and Perish software. The core input of this study is analysing available information to address resilience issues in mitigating risk in the sustainable supply chain. To build a more sustainable system, it offers suggestions for more research in these areas that scholars may pursue and that project stakeholders could implement in their organisations.